Development and Study of Hard-Facing Materials on the Base of Heat-Resisting High-Hardness Steels for Plasma-Jet Hard- Facing in Shielding-Doping Nitrogen Atmosphere; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Malushin N. N.; Kovalev A. P.; Valuev D. V. Denis Viktorovich; Shats E. A.; Borovikov I. F. (2016, 2016)
Title screen